The savage, noble death of Babs Dionne [large type] - Currie, Ron, Jr., 1975- (Thorndike Press, a part of Gale, a Cengage Company, 2025)
"Babs Dionne, proud Franco-American, doting grandmother, and vicious crime matriarch, rules her small town of Waterville, Maine, with an iron fist. She controls the flow of drugs into Little Canada with the help of her loyal lieutenants, girlfriends since they were teenagers, and her eldest daughter, Lori, a Marine vet struggling with addiction. When a drug kingpin discovers that his numbers are down in the upper northeast, he sends a malevolent force, known only as The Man, to investigate. At the same time, Babs's youngest daughter, Sis, has gone missing, which doesn't seem at all like a coincidence. In twenty-four hours, Sis will be found dead, and the whole town will seek shelter from Babs's wrath."--